(untitled) - Hakusho, Kagakuijutsu (Tokyo, 1983)
This book covers the whole activities in the science and technology field in Japan. This book is the appropriate guidance for Japanese policies.
Keywords: Science,Technology,Khoa học,Công nghệ; Japan,Japan,Nhật Bản,Nhật Bản